Improved facial nerve identification during parotidectomy with fluorescently labeled peptide. (12th May 2016) - Hussain, Timon; Nguyen, Linda T.; Whitney, Michael; Hasselmann, Jonathan; Nguyen, Quyen T.
Abstract : Objectives/Hypothesis: Additional intraoperative guidance could reduce the risk of iatrogenic injury during parotid gland cancer surgery. We evaluated the intraoperative use of fluorescently labeled nerve binding peptide NP41 to aid facial nerve identification and preservation during parotidectomy in an orthotopic model of murine parotid gland cancer. We also quantified the accuracy of intraoperative nerve detection for surface and buried nerves in the head and neck with NP41 versus white light (WL) alone. Study Design: Twenty‐eight mice underwent parotid gland cancer surgeries with additional fluorescence (FL) guidance versus WL reflectance (WLR) alone. Eight mice were used for additional nerve‐imaging experiments. Methods: Twenty‐eight parotid tumor‐bearing mice underwent parotidectomy. Eight mice underwent imaging of both sides of the face after skin removal. Postoperative assessment of facial nerve function measured by automated whisker tracking were compared between FL guidance (n = 13) versus WL alone (n=15). In eight mice, nerve to surrounding tissue contrast was measured under FL versus WLR for all nerve branches detectable in the field of view. Results: Postoperative facial nerve function after parotid gland cancer surgery tended to be better with additional FL guidance. Fluorescent labeling significantly improved nerve to surrounding tissue contrast for both large and smaller buried nerve branches compared to WLR visualization and improved detection sensitivity and specificity. Conclusions: NP41 FL imaging significantly aids the intraoperative identification of nerve braches otherwise nearly invisible to the naked eye. Its application in a murine model of parotid gland cancer surgery tended to improve functional preservation of the facial nerve. Level of Evidence: NA Laryngoscope, 126:2711–2717, 2016